Modified Homotopy Perturbation Technique for the Approximate Solution of Nonlinear Equations. (18th February 2014) - Shah, Farooq Ahmed
Abstract : We use a new modified homotopy perturbation method to suggest and analyze some new iterative methods for solving nonlinear equations. This new modification of the homotopy method is quite flexible. Various numerical examples are given to illustrate the efficiency and performance of the new methods. These new iterative methods may be viewed as an addition and generalization of the existing methods for solving nonlinear equations.